Human resource management - Mathis, Robert L. (Thomson South-Western, 2004)
Organizations globally today face many challenges, and the globalization of human resource (HR) management is growing in significance for employers throughout the world. This book has been reproduced to provide students and readers throughout the world with a text appropriate for global usage